Enhancing Students' Religiosity in Educational Context: A Mixed-Methods Study in Islamic High School - Mangestuti, Retno; Aziz, Rahmat (Universitas Muhammadiyah Yogyakarta, 2023)
Cultivating religiosity among students in schools is a crucial initiative that should be implemented. The research aims to evaluate the impact of school climate on students' development of religiosity. The research methodology used mixed-method explanatory models to evaluate theories on school climate's influence on religiosity and explore teachers' strategies to develop students' religiosity within schools. Quantitative data was collected from 482 students at junior and senior schools, and qualitative data was gathered from six randomly selected teachers. Quantitative data was collected using school climate and religiosity scales. Descriptive and regression analyses were used to analyze the quantitative data, while thematic analysis was used for the qualitative data. The regression analysis results showed a value of R = 0.338, R2 = 0.114, p 0.005, indicating a positive impact of school climate on students' religiosity. Teachers employ six approaches to achieve this goal: habituation, guidance, leading by example, attention to individual students' needs, creating a positive atmosphere, and providing educational sanctions. These results highlight the importance of improving teachers' expertise in promoting student religiosity. Experimental research could be an effective alternative for further advancing this type of study.